Examen especial a las políticas de control interno a la cuenta inventarios en la zapatería Toxic en el periodo 2017. - Lucero Balcazar, Maritza Gabriela (My University, 2018)
The audits are of vital importance in the companies, nowadays they are considered as a functional tool for the same, in the present work it was decided to carry out the special examination of the inventories account and the control policies that are employed in the Shoe Store "Toxic" "In the 2017 period, it must be carried out by a professional who has the knowledge and experience necessary to carry out the responsible work in a responsible manner, giving security to the owners of the businesses or entrepreneurs when receiving the results of the audit, they will have the confidence to make timely decisions according to the recommendations issued by the auditor. The qualitative methodology will be the most appropriate for the development of the work, so it answers questions such as why? What? How? And for what?, starting the interpretation of the information provided by the techniques applied, to use will be the questionnaire, research that will obtain and collect evidence of control of the inputs and outputs of the goods. Know the procedures for the execution of the financial audit, through information obtained from standards established as International Standards Audit 200 and 400, Generally Accepted Auditing Standards. Establish policies that allow the correct accounting control and the physical merchandise that enters and leaves the company. The method of the questionnaire will be applied to evaluate the internal control that allows obtaining and collecting evidences of the control of the entrances and exits of the merchandise.
Las auditorias son de vital importancia en las empresas, hoy en día son consideradas como una herramienta funcional para las mismas, en el presente trabajo se decidió realizar el examen especial de la cuenta inventarios y las políticas de control que son empleadas en la Zapatería “Toxic” en el periodo 2017, debe ser realizado por un profesional que tenga los conocimientos y experiencia necesaria para desempeñar el trabajo encargado de manera responsable, dando seguridad a los dueños de los negocios o los empresarios al momento de recibir los resultados de la auditoria, tendrán la confianza para tomar decisiones oportunas de acuerdo a las recomendaciones emitidas por el auditor. La metodología cualitativa será la más apropiada para el desarrollo del trabajo, por lo que responde a preguntas como ¿Por qué? ¿Qué? ¿Cómo? y ¿Para qué?, dando comienzo a la interpretación de la información proporcionada mediante las técnicas aplicadas, a utilizar será el cuestionario, de investigación que permitirán obtener y recolectar evidencias del control de las entradas y salidas de las mercaderías. Conocer los procedimientos para la ejecución de la auditoría financiera, a través de información obtenida de normas establecidas como Normas Internacionales Auditoria 200 y 400, Normas Auditoria Generalmente Aceptadas. Establecer políticas que permitan el correcto control contable y de la mercadería física que entra y sale de la empresa. Se aplicará el método del cuestionario para evaluar el control interno que permitan obtener y recolectar evidencias del control de las entradas y salidas de las mercaderías.
Keywords: AUDITORIA; CONTROL; EVALUAR; EXAMEN ESPECIAL